2020
DOI: 10.1007/s13592-020-00754-5
|View full text |Cite
|
Sign up to set email alerts
|

Social benefits require a community: the influence of colony size on behavioral immunity in honey bees

Abstract: Emergent properties of eusocial insect colonies (e.g., nest architecture and defense) highlight benefits of group living. Such emergent properties, however, may only function as a benefit if the group is large enough. We tested the effect of group size on colony-level fever in honey bees. When a colony is infected with Ascosphaera apis , a heat-sensitive brood pathogen, adult bees raise the temperature to kill the pathogen and keep brood disease free. In relatively large colonies, we show a rhythm to honey bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…Starks et al [20] laid the foundation for understanding the phenomenon of behavioral, or social fever, as a response to challenge with the fungal pathogen, A. apis, in honey bees. Few studies have since followed this report, describing a novel form of social immunity [21,29]. Results from our study affirmed that honey bees increase the temperature of the brood nest after exposure to A. apis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Starks et al [20] laid the foundation for understanding the phenomenon of behavioral, or social fever, as a response to challenge with the fungal pathogen, A. apis, in honey bees. Few studies have since followed this report, describing a novel form of social immunity [21,29]. Results from our study affirmed that honey bees increase the temperature of the brood nest after exposure to A. apis.…”
Section: Discussionsupporting
confidence: 76%
“…After experimental inoculation of small colonies with A. apis [20], a modest (but significant) deviation from expected brood temperature (+0.56 • C) was observed, which suggested that adult workers generate a behavioral fever. Ascosphaera apis is temperature-sensitive; therefore, the adult-driven increase in brood nest temperature was hypothesized to kill the pathogen and prevent its spread among uninfected immature nestmates [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Відомо, що бджолині колонії, особливо у весняноосінній періоди, вразливі щодо збудників бактеріальних та вірусних інфекцій. Після зимівлі суттєво зни-жується рівень напруженості колективного імунітету бджіл (Bonoan et al, 2020;Harwood et al, 2021;Laomettachit et al, 2021;Morfin et al, 2021), що призводить до порушень у роботі їхньої травної системи з проявами діареї (Kešnerová et al, 2020;Lakhman et al, 2021). Синдром диспепсії у бджіл характеризується різким зниженням продуктивності, що суттєво впливає на рівень рентабельності приватних пасік.…”
Section: вступunclassified
“…Honey bee colonies may also behaviorally increase their temperature to induce a "fever" which is hypothesized to be a generalized response to illness, particularly in large colonies (Simone-Finstrom et al, 2014;Bonoan et al, 2020). Colonies with the fungal infection Ascosphaera apis behaviorally increase their temperature (Starks et al, 2000), while individuals infected by Nosema ceranae seek high temperature areas within the colony (Campbell et al, 2010).…”
Section: Mechanisms For Warming the Hivementioning
confidence: 99%